2021
DOI: 10.4037/aacnacc2021454
|View full text |Cite
|
Sign up to set email alerts
|

Battling Burnout at the Frontlines of Health Care Amid COVID-19

Abstract: Nursing is a physically and emotionally demanding profession. Grueling job roles and challenging work environments, specifically in acute or critical care settings, place health care professionals at risk of burnout. Burnout in health care professionals results from a chronic negative work experience, leading to job dissatisfaction and, ultimately, poor patient outcomes. Symptoms and prevalence of burnout can be alleviated by implementing individual-focused strategies and minor modifications in work environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…Inevitably, HCWs experienced immense pressure and eventually burnout, which is a major contributor to turnover intention [ 55 ]. Burnout accompanies the progression of emotional overburdening, deteriorating mental well-being, and job dissatisfaction, which may drive HCWs to conclude that resignation is their best option [ 80 ]. In hindsight, these phenomena could be alleviated by judicious considerations of the consequences and the initiation of mitigating health policy measures.…”
Section: Discussionmentioning
confidence: 99%
“…Inevitably, HCWs experienced immense pressure and eventually burnout, which is a major contributor to turnover intention [ 55 ]. Burnout accompanies the progression of emotional overburdening, deteriorating mental well-being, and job dissatisfaction, which may drive HCWs to conclude that resignation is their best option [ 80 ]. In hindsight, these phenomena could be alleviated by judicious considerations of the consequences and the initiation of mitigating health policy measures.…”
Section: Discussionmentioning
confidence: 99%
“…Using person centredness as a theoretical framework, they found that the pandemic made best practice difficult for nurse leaders as they had to adapt their leadership. Some thrived and innovated to new ways of working, whereas others struggled with a crisis of leader (Allen, 2020;Brodrick et al, 2020;Digby et al, 2021;Fortgang, 2021;Markey et al, 2021;Moore, 2020;Quinn et al, 2021;Raderstorf et al, 2020;Rossa et al, 2020;Rosser et al, 2020;Vogel & Flint, 2021) M: Multiple communication methods (listening, being present, team huddles, protocols, emails, zoom, Schwartz Rounds, collaborative dialogue, horizontal and vertical communication (Abbu, 2021;Allen, 2020;Brodrick et al, 2020;Catania et al, 2021;Croke, 2020;Digby et al, 2021;Dimino et al, 2020;Ernst, 2020;Fortgang, 2021;Hoffmann et al, 2020;Hofmeyer & Taylor, 2021;Holge-Hazelton et al, 2021;Howell, 2021;…”
Section: Being Open and Engagingmentioning
confidence: 99%
“…M: Multiple communication methods (listening, being present, team huddles, protocols, emails, zoom, Schwartz Rounds, collaborative dialogue, horizontal and vertical communication (Abbu, 2021; Allen, 2020; Brodrick et al, 2020; Catania et al, 2021; Croke, 2020; Digby et al, 2021; Dimino et al, 2020; Ernst, 2020; Fortgang, 2021; Hoffmann et al, 2020; Hofmeyer & Taylor, 2021; Holge‐Hazelton et al, 2021; Howell, 2021; Markey et al, 2021; Merchant, 2021; Moore, 2020; Rossa et al, 2020; Vogel & Flint, 2021; Yoder‐Wise et al, 2021)…”
Section: Data Extractionmentioning
confidence: 99%
“…The global Coronavirus disease 2019 (COVID-19) pandemic has resulted in an influx of acute critical illness patients requiring basic and advanced life support in the intensive care unit [ 53 ]. To expand critical care capacity and maximize safety for everybody, critical care leaders have battled with difficult decisions about which services should be emphasized, which should be curtailed, and which should be stopped in preparation for the expected surge of patients with COVID-19 [ 54 ]. Although critical care research is always vital, it is a top priority worldwide during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%